PERKEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH 2013-2023 (STUDI DI MADRASAH TSANAWIYAH) - Nuwairah, Khaleyda Mariza (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
Abstract Education in Indonesia has experienced a recession from the Dutch colonial era to the present day. In an education that is part of an important aspect is curriculum. Since the era of the new order has undergone eight curriculum changes, from the curriculum of 1968 to the now thr curricular independent study. Each curriculum has its own characteristics, including the Curriculum 2013. The Method of research carried out is the study of the library by taking reference sources of books and journal articles relevant to the title. The results of the study show in the 2013 curriculum or the independent curricular there is definitely an evolution in terms of curricula based on the continous development of iptek. Than for the islamic religion education subjects that exist in Madrasah consist of four groups all regulated by the regulation of the Minister of Religion under the auspices of the Ministry of Religions.  Keywords: Curriculum, Education, Madrasah.  Abstrak Pendidikan di Indonesia telah mengalami pasang surut dari zaman penjajah Belanda hingga sekarang. Dalam sebuah pendidikan, yang termasuk dalam aspen penting yaitu Kurikulum. Sejak zaman orde baru telah mengalami delapan kali perubahan kurikulum, dari kurikulum tahun 1968 sampai sekarang kurikulum merdeka belajar. Setiap kurikulum yang dijalankan tentunya memiliki ciri tersendiri termasuk kurikulum 2013 dan kurikulum merdeka belajar. Metode penelitian yang dilakukan berupa kajian kepustakaan dengan mengambil sumber rujukan buku dan artikel jurnal yang relevan dengan judul yang diangkat. Hasil dari penelitian menunjukkan bahwa pada kurikulum 2013 ataupun kurikulum merdeka tentunya ada perkembangan dalam hal kurikulum berdasarkan terus berkembangnya iptek. Lalu mata pelajaran pendidikan Agama Islam yang terdapat pada Madrasah terdiri dari empat rumpun semuanya diatur oleh peraturan Menteri Agama di bawah naungan Kementerian Agama. Kata Kunci: Kurikulum, Madrasah, Pendidikan.